Grassflies of the subfamily Chloropinae (Diptera: Chloropidae) from Vietnam and Thailand, with descriptions of two new species - Nartshuk, E. P. (Zootaxa, 2013)
Seven genera of Chloropinae (Diptera: Chloropidae) from Vietnam and Thailand are discussed: Eurina Meigen (1 species), Chloromerus Becker (1 species), Siphlus Loew (1 species), Neoloxotaenia Sabrosky (3 species), Aragara Walker (1 species), Elachiptereicus Becker (1 species), Lagaroceras Becker (1 species). Some of them are new to the fauna of Vietnam and Thailand. Two new species are described: Chloromerus orientalis n. sp. from Thailand, and Lagaroceras tulense n. sp. from Vietnam and Thailand. The genus Chloromerus Becker, 1911 is recorded for the first time in the Oriental Region. The genus Semaranga Becker, 1911 is synonymised with Elachiptereicus Becker, 1909—syn. nov. A key to the Palaearctic and Oriental species of Lagaroceras Becker, 1903 is given.